Advanced technological integration for swine wastewater: Enhancing treatment with photo-Fenton and electrocoagulation - Tatiana Luque; María Jimenez; Anyie Aguilar; Brayan A. Parra-Orobio; Jesús Alvarez; Angelica Hernandez; Cristian Mejia-Parada; Viviana Mora-Ruiz; Claudia Tavera -Ruiz; Jonathan Soto-Paz (Results in Engineering)
The increase in pork consumption and its reputation as one of the best sources of protein has led to growth in this industry, however, its production generates a significant amount of swine wastewater (SWW). Conventional biological treatment methods are typically used to treat SWW. However, their applicability in small and medium sized enterprises (SMEs) in the swine industry is limited due to their high space requirements. Therefore, advanced oxidation processes (AOPs) such as photofenton (PF) and electrocoagulation (EC) represent a potential alternative for SWW treatment due to their lower space requirements. The aim of this study was to treat SWW by integrating the PF process followed by EC as a technological couple to optimize the removal efficiency of pollutants present in SWW. Experiments were conducted in a 2 L batch reactor, examining the effects of hydrogen peroxide (H2O2) concentration (0.5, 2.5, 5.0 g L−1) and current density (10, 50, 90 A m−2) on pH, organic matter, nutrients, and germination index (GI). The results showed that the optimum process conditions correspond to 2.6 g L−1 H2O2 and a current density of 41 A m−2. Under these conditions, an effluent is obtained with pH values of 7.8, TSS of 385 mg L−1, COD of 254 mg L−1, BOD5 of 139.8 mg L−1, TN of 190.4 mg L−1 and GI of 117 %. The results showed that the effluent complies with the Colombian standards. From a cost perspective, the use of Photo-Fenton to treat wastewater under these conditions would be US$ 0.7 per liter.